Diagnostic utility of reflux disease symptoms. (13th April 2004) - Shaw, M
Abstract : Symptom assessment, by structured interview or questionnaire, is central to the diagnosis of gastro-oesophageal reflux disease (GORD). However, empiric support for the diagnostic utility of reflux symptom measures is lacking. Reliable reflux symptom questionnaires have been developed with content validity. These questionnaires need to be evaluated in terms of diagnostic accuracy, support for application of specific treatment, and improved outcomes resulting from their use. The impact on clinical outcomes of GORD diagnosis by valid questionnaires or structured interview has not been studied.